Effects of different drying process, extraction and encapsulation agents on stability of Alternanthera sessilis (L.) DC. Extract / Syafiqah Shaharuddin - Shaharuddin, Syafiqah (2023)
There are numerous studies evaluating the effectiveness of innovative drying methods and alternative extraction methods, yet only a few reported the effect of the combination of these two. Therefore, in this study, the relationships between drying methods and extraction methods on antioxidant properties, total betalain and colour of A. sessilis red were displayed. Drying of A. sessilis red was performed through superheated-steam drying (SSD) and freeze-drying (FD) which was later followed by the extraction using conventional extraction and ultrasonic-assisted extraction (UAE). Results showed that combining SSD and UAE produced greater yield of extract (32.19%) with higher phenolic compounds (GA: 1715.75 mg/100g DS; VA: 230.41 mg/100g DS; PCA: 1559.96 mg/100g DS) and antioxidant capacity (DPPH : 39.48%; FRAP : 1015.02 mg TE/100g DS) as well as having good colour. Still, a combination of SSD (170°C; 1 hour) and UAE (30 mins; 20-kHz; 40°C) was unable to enhance the betalain content. Hence, the stability study was proceeded using FD and UAE. Yet, betalain can still undergo degradation, causing the loss of its colour. The encapsulation technique can improve the stability of the pigment but it requires the addition of carrier agents. This study focused on the effect of different carrier agents on the antioxidative properties, total betalain and colour of A. sessilis red powder to its powder properties. The liquid extracts of A. sessilis red were added with single carrier agent (maltodextrin) as well as binary carrier agents (maltodextrin+arabic gum, maltodextrin+whey protein isolate) at a percentage of 20% w/w prior to encapsulation by the spray drying. The incorporation of carrier agent yielded powder of higher yield (27.80%-34.35%) and glass transition temperature (42.50°C-55.28°C) as well as lower hygroscopicity (13.40%-17.29%), moisture content (3.20% - 4.10%) and water activity (0.37-0.26). The use of binary carrier agents also improves the morphology of the powder by reducing the formation of cracks on the microcapsules. Even so, storing the powders for two months at temperatures of 4°C, 25°C and 40°C with the exclusion of oxygen (oxygen absorber) and light (opaque aluminium packaging) still caused detrimental impacts to the antioxidant properties and betalain pigment. Combinations of maltodextrin and AG were seen to be the best carrier agent as they showed the highest retention of betalain pigment (betanin: 74.36%- 84.62%; betaxanthin: 52.94%-90.20%) and moderate retention of antioxidant capacity (DPPH: 70.70%-77.39%; FRAP: 50.00%-80.60%).